PERANCANGAN USER INTERFACE DIGITALISASI ANALISIS KELENGKAPAN REKAM MEDIS MENGGUNAKAN METODE DESIGN THINKING DI RSUD PALEMBANG BARI - Dian Yuliani; Anastasia Cyntia Dewi Kurniawati; Hosizah Hosizah; Arief Ichwan (Smart Education, 2025)
Abstract: The mandatory of Electronic Medical Records (EMR) in Indonesia encourages Health Information Recorders (HIMs) to find the best solution to maintain the quality of EMR. Although EMR has been implemented, the electronic system in hospitals does not have enough features for effective quality assurance, resulting in difficulties for HIMs in quantitative and qualitative analysis. Based on KMK HK.01.07/Menkes/1128/2022 on Hospital Accreditation Standards, if the electronic system does not support service quality assurance operations, system development is required. This study aims to design a User Interface (UI) for digitizing the completeness analysis of Medical Records (MR). The method used is design thinking with five UI principles (proximity, similarity, continuity, figure and background and common fate). Design testing using heuristic evaluation by five evaluators. The result was a UI with features of MR completeness analysis, notification, MR completeness analysis report and activity log. The three highest heuristic principles were Help and Documentation score 2.80 (major), Recognition Rather Than Recall score 2.20 (minor) and Help Users Recognize, Diagnose and Recover from Errors score 1.60 (minor). These principles have been improved according to the evaluator's recommendations. It is recommended to improve the UI to achieve a score of 0 (no problem). Keyword: Heuristic Evaluation, Medical Record Completeness Analysis, User Interface Abstrak: Kewajiban Rekam Medis Elektronik (RME) di Indonesia mendorong para Perekam Medis dan Informasi Kesehatan (PMIK) mencari solusi terbaik untuk menjaga kualitas RME. Meskipun RME telah diterapkan, sistem elektronik di Rumah Sakit (RS) belum memiliki fitur yang cukup untuk penjaminan mutu yang efektif, mengakibatkan PMIK kesulitan dalam analisis kuantitatif dan kualitatif. Berdasarkan KMK HK.01.07/Menkes/1128/2022 tentang Standar Akreditasi RS, bila sistem elektronik tidak mendukung operasional penjaminan mutu pelayanan, pengembangan sistem diperlukan. Penelitian ini bertujuan merancang User Interface (UI) digitalisasi analisis kelengkapan Rekam Medis (RM). Metode yang digunakan adalah design thinking dengan lima prinsip UI (proximity, similarity, continuity, figure and background dan common fate). Pengujian desain menggunakan evaluasi heuristik oleh lima evaluator. Hasil penelitian adalah UI dengan fitur analisis kelengkapan RM, notification, report analisis kelengkapan RM dan log aktivitas. Diperoleh tiga prinsip heuristik tertinggi yakni Help and Documentation skor 2,80 (major), Recognition Rather Than Recall skor 2,20 (minor) dan Help Users Recognize, Diagnose and Recover from Errors skor 1,60 (minor). Prinsip-prinsip tersebut telah diperbaiki sesuai rekomendasi evaluator. Disarankan untuk menyempurnakan UI guna mencapai skor 0 (no problem). Kata Kunci: Analisis Kelengkapan Rekam Medis, Evaluasi Heuristik, User Interface